2021
DOI: 10.3390/w13121632
|View full text |Cite
|
Sign up to set email alerts
|

Field Scale Demonstration of Fly Ash Amended Bioretention Cells for Stormwater Phosphorus Removal: A Review of 12 Years of Work

Abstract: In 2007, ten bioretention cells were constructed in Oklahoma as part of a full-scale technology project to demonstrate stormwater phosphorus reduction. The filter media used was amended with 5%, Class C fly ash by weight to increase phosphorus and heavy metal retention. In 2014, core samples were collected from four of the cells, and three were instrumented for continuous water monitoring for the following year. This paper will review the design, construction, computer modeling of phosphorus retention, and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similarly, wollastonite, a naturally occurring mineral that is also high in iron and aluminum oxide, showed good P removal capabilities in swimming and fishpond systems (82%-96% removal) (Fondu et al 2015) and vertical upflow columns of secondary wastewater (80%-96% removal) (Brooks et al 2000). However, even with very high P removal levels, the effluent P in most studies exceeded the FLL-suggested levels of 0.01 mgÁL À1 (e.g., 0.03 mgÁL À1 with fly ash-sand bioretention media blend) (Vogel et al 2021) and 0.015 mg•L À1 with sandy loam amended with 15% air-dried water treatment residual (Qiu et al 2019). In a few cases, sand and compost bioretention media mixed with activated alumina achieved 0.01 mgÁL À1 (Ali and Pickering 2023).…”
mentioning
confidence: 79%
“…Similarly, wollastonite, a naturally occurring mineral that is also high in iron and aluminum oxide, showed good P removal capabilities in swimming and fishpond systems (82%-96% removal) (Fondu et al 2015) and vertical upflow columns of secondary wastewater (80%-96% removal) (Brooks et al 2000). However, even with very high P removal levels, the effluent P in most studies exceeded the FLL-suggested levels of 0.01 mgÁL À1 (e.g., 0.03 mgÁL À1 with fly ash-sand bioretention media blend) (Vogel et al 2021) and 0.015 mg•L À1 with sandy loam amended with 15% air-dried water treatment residual (Qiu et al 2019). In a few cases, sand and compost bioretention media mixed with activated alumina achieved 0.01 mgÁL À1 (Ali and Pickering 2023).…”
mentioning
confidence: 79%
“…However, bioretention performance can fluctuate [80] and can even increase the concentrations of pollutants [81] and nutrients [53]. Operativity can improve with age [82] and some modifications [83]; fly ash amendments improved microbial removal in bioretention cells [84] and are an effective option for phosphorus removal [85], as a retrofitted upflow filter [86]. Bioretention acts as both a nitrogen source and sink (by infiltration and plant uptake mainly) [87].…”
Section: Regulation Services: Water Qualitymentioning
confidence: 99%